2015
DOI: 10.1021/acs.jproteome.5b00283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Api88 Binding Partners in Escherichia coli Using a Photoaffinity-Cross-Link Strategy and Label-Free Quantification

Abstract: Gene-encoded antimicrobial peptides (AMPs) kill bacteria very efficiently by either lytic mechanisms or inhibition of specific bacterial targets. Proline-rich AMPs (PrAMPs), for example, produced in insects and mammals rely on the second mechanism. They bind to the 70 kDa bacterial heat shock protein DnaK and the 60 kDa chaperonin GroEL and interfere with protein folding, but this does not explain their strong bactericidal effects. Thus, we looked for further binding partners of apidaecin 1b, originally identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Thus, it represents a universal lead structure for developing broadband antibiotics. This broad activity spectrum assumed from the K d values is supported by experimental data presented in the first publication about oncocins and their antibacterial activity . The authors showed that Onc72 and Api88 are highly active against a broad panel of 37 clinical isolates of E. coli , K. pneumoniae , P. aeruginosa , A. baumannii , Enterobacter cloacae , and Proteus vulgaris with MIC values ranging from 0.125 to 8 mg/L .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, it represents a universal lead structure for developing broadband antibiotics. This broad activity spectrum assumed from the K d values is supported by experimental data presented in the first publication about oncocins and their antibacterial activity . The authors showed that Onc72 and Api88 are highly active against a broad panel of 37 clinical isolates of E. coli , K. pneumoniae , P. aeruginosa , A. baumannii , Enterobacter cloacae , and Proteus vulgaris with MIC values ranging from 0.125 to 8 mg/L .…”
Section: Resultsmentioning
confidence: 62%
“…However, PrAMPs will likely bind to other intracellular proteins as well. Recently, we reported that Api88, a close analogue of Api137, binds in vivo to nonribosomal proteins, such as DnaK and GroEL . DnaK was identified as an intracellular target of PrAMPs including apidaecins and oncocins, but the binding is much weaker than for ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Api137 suppresses the assembly of the 50S subunitb y binding either to ap artially assembled 50S subunit lacking some 50S proteins (e.g.,p 2 50S with an sedimentation coefficient of % 40-43S [8] )o ro ne protein of the 50S subunit that plays ak ey role in the late assembly of the 50S subunit: [9] for example, ribosomal protein L3, identified as potential binding partner of apidaecins. [10] This model explains the minor effects observed fori nv itro translation, which relies on assembled 50S subunits,a nd the strongi nhibitory effect in vivo when the 50S subunits are constantly assembled in the cells. Interestingly,e rythromycin also interferesw ith the 50S subunit assembly, although its antibacterial effect is mostly attributed to inhibition of the 50S subunit.…”
mentioning
confidence: 88%
“…For example, Volke et al. devised benzophenone and alkyne‐tagged versions of proline‐rich antimicrobial peptides and found that these labeled ribosomal proteins in E. coli …”
Section: Photoaffinity Labelingmentioning
confidence: 99%